Construction of dna vaccine expressing msp-1c of plasmodium falciparum - Noraini, Mat Yunus (Universiti Sains Malaysia, 2008)
Malaria is one of the most threatening parasitic diseases, being endemic in most of the tropical and subtropical countries. This problem becomes severe with the rapid spread of drug resistant Plasmodium falciparum, development of resistance to insecticides by Anopheles mosquito, poor hygienic care, socioeconomic problems and transition of people. Therefore an effective and universal malaria vaccine against Plasmodium falciparum should be developed. A great deal effort of researchers nowadays has been focused on vaccines targeting at the asexual blood stage due to prolong life cycle within the blood and it can directly reduce morbidity and mortality associated with malarial disease in human4 One of the vaccine candidates from asexual blood stage is a 19 kDa Cterminal region of merozoite surface protein 1 (MSP-1C). MSP-1C protein has been considered as a good candidate for malaria vaccine development due to their obvious accessibility by host's immune response. The purpose of this project is to construct a DNA vaccine expressing MSP-1 C of P. falciparum, In order to develop this vaccine; MSP-1 C fragment was amplified from plasmid pNMN016 by using polymerase chain reaction (PCR). The MSP-1C fragment was ligated into pVAX1, a plasmid vector that is designed for use in the development of DNA vaccines. Hopefully, the development of DNA vaccine against P. falciparum would decline the number of malaria cases worldwide.